Early self-managed focal sensorimotor rehabilitative training enhances functional mobility and sensorimotor function in patients following total knee replacement: a controlled clinical trial. (July 2018) - Moutzouri, Maria; Gleeson, Nigel; Coutts, Fiona; Tsepis, Elias; Gliatis, John
Objective: To assess the effects of early self-managed focal sensorimotor training compared to functional exercise training after total knee replacement on functional mobility and sensorimotor function. Design: A single-blind controlled clinical trial. Setting: University Hospital of Rion, Greece. Subjects: A total of 52 participants following total knee replacement. Outcome measures: The primary outcome was the Timed Up and Go Test and the secondary outcomes were balance, joint position error, the Knee Outcome Survey Activities of Daily Living Scale, and pain. Patients were assessed on three separate occasions (presurgery, 8 weeks post surgery, and 14 weeks post surgery). Intervention: Participants were randomized to either focal sensorimotor exercise training (experimental group) or functional exercise training (control group). Both groups received a 12-week home-based programme prescribed for 3–5 sessions/week (35–45 minutes). Results: Consistently greater improvements ( F 2, 98  = 4.3 to 24.8; P  < 0.05) in group mean scores favour the experimental group compared to the control group: Timed Up and Go (7.8 ± 2.9 seconds vs. 4.6 ± 2.6 seconds); balance (2.1 ± 0.9° vs. 0.7 ± 1.2°); joint position error (13.8 ± 7.3° vs. 6.2 ± 9.1°); Knee Outcome Survey Activities of Daily Living Scale (44.2 ± 11.3 vs. 26.1 ± 11.4); and pain (5.9 ± 1.3 cm vs. 4.6 ± 1.1 cm). Patterns of improvement for the experimental group over time were represented by a relative effect size range of 1.3–6.5. Conclusions: Overall, the magnitude of improvements in functional mobility and sensorimotor function endorses using focal sensorimotor training as an effective mode of rehabilitation following knee replacement.